2019
DOI: 10.4315/0362-028x.jfp-18-235
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Salmonella Heidelberg after Exposure to Cetylpyridinium Chloride, Acidified Calcium Hypochlorite, and Peroxyacetic Acid

Abstract: The application of RNA sequencing in commercial poultry could facilitate a novel approach toward food safety with respect to identifying conditions in food production that mitigate transcription of genes associated with virulence and survivability. In this study, we evaluated the effects of disinfectant exposure on the transcriptomes of two field isolates of Salmonella Heidelberg (SH) isolated from a commercial broiler processing plant in 1992 and 2014. The isolates were each exposed separately to the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Among the 90 genes associated with virulence, pathogenicity, and resistance (VPR) in wild-type S. Heidelberg, 10.0% (9 of 90 genes) or 23.3% (21 of 90 genes) of VPR genes were upregulated after exposure to CPC in 2014 and 1992 serovar S. Heidelberg field strains. They concluded that genes which can make multiple antibiotic-resistant proteins and multidrug-resistant proteins were mainly upregulated in CPCtreated S. Heidelberg (64).…”
Section: Figmentioning
confidence: 99%
“…Among the 90 genes associated with virulence, pathogenicity, and resistance (VPR) in wild-type S. Heidelberg, 10.0% (9 of 90 genes) or 23.3% (21 of 90 genes) of VPR genes were upregulated after exposure to CPC in 2014 and 1992 serovar S. Heidelberg field strains. They concluded that genes which can make multiple antibiotic-resistant proteins and multidrug-resistant proteins were mainly upregulated in CPCtreated S. Heidelberg (64).…”
Section: Figmentioning
confidence: 99%
“…However, the mechanisms of transfer of disinfectant resistance genes remain unclear, and only a few have been described (Mc Carlie et al 2020). Cross-resistance between antimicrobial substances is becoming an increasing concern because of the possible positive correlation between resistance to disinfectants and resistance to antibiotics (Cadena et al 2019, Mc Carlie et al 2020. The major concern is based on the hypothesis that disinfectant exposure can promote antibiotic resistance, thus generating MDR bacteria (Mc Carlie et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another report evaluates the differential expression of genes in birds infected with Salmonella Typhimurium, finding genes related to the immune response, IgA production, activation of the Toll-like signaling receptor pathway, and cytokine-cytokine interactions [ 11 ]. Cadena and collaborators identify genes over-expressed in Salmonella Heidelberg when it is subjected to different disinfectants, finding some related to virulence, pathogenicity, and resistance, allowing with this identification to make recommendations for the control of Salmonella [ 199 ].…”
Section: The –Omics As a Tool For Salmonella Strategies Developmentmentioning
confidence: 99%